Decision Support System for Giving Kredit Usaha Rakyat Using the Moora Method - Aulya, Novi; Adawiyah, Rabiah; Pasrun, Yuwanda Purnamasari; Nirsal, Nirsal (Jurnal Media Informasi Teknologi, 2024)
People's Business Credit (KUR) is credit or financing in the form of working capital or investment aimed at MSMEs (micro, small and medium enterprises and cooperatives) in productive and viable but not yet bankable businesses with a loan ceiling of up to IDR 500,000,000. 00 guaranteed by the guarantor company. The difficulty faced in determining the prospective beneficiary is that the staff in the utilization section takes a long time to verify the files of the prospective people's business credit recipients. Therefore, an application is needed that can help staff of Bank BRI KCP Lapai, North Kolaka Regency, in determining credit recipients, namely a decision support system. This application is made by applying the MOORA method, the MOORA method is a method that has calculations with minimum and very simple calculations. This method has a good level of selectivity in determining an alternative. The approach taken by MOORA is defined as a process simultaneously to optimize two or more conflicting constraints. Based on the results of system testing using sample data that has been carried out on the Decision Support System, it produces 4 data , 1 data is feasible and 3 data is not feasible.